Microwave Liquid Crystal Technology - Holger Maune; Matthias Jost; Roland Reese; Ersin Polat; Matthias Nickel; Rolf Jakoby (Crystals, 2018)
Tunable Liquid Crystal (LC)-based microwave components are of increasing interest in academia and industry. Based on these components, numerous applications can be targeted such as tunable microwave filters and beam-steering antenna systems. With the commercialization of first LC-steered antennas for Ku-band e.g., by Kymeta and Alcan Systems, LC-based microwave components left early research stages behind. With the introduction of terrestrial 5G communications systems, moving to millimeter-wave communication, these systems can benefit from the unique properties of LC in terms of material quality. In this paper, we show recent developments in millimeter wave phase shifters for antenna arrays. The limits of classical high-performance metallic rectangular waveguides are clearly identified. A new implementation with dielectric waveguides is presented and compared to classic approaches.